(3efXhQ Sdhcj hGSJQGJjLjs - (3RcQjG eWdc(B, (3GdOhQjs; (3CMeO Ydj UGdM(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2009)
(3GdeQJcRGJ GdacQjI dGOGQI GdGYeGd GdOhdjI, NUGFU cjGfGJ efXeGJ GdGYeGd GdOhdjI, GdGWGQ GdKbGaj ddEOGQI GdOhdjI, GdGWGQ GdKbGaj ddGOGQI GdOhdjI, GdeYeGQjI GdJfXjejI ddGOGQI GdOhdjI, GdbjGOI GdOhdjI, OhGaY heOGNd UjGZI GdGSJQGJjLjI GdOhdjI, efgLjI UjGZI GdGSJQGJjLjI GdOhdjI, GOGQI GdehGQO GdHTQjI GdOhdjI, GOGQI GdJShjb GdOhdj, GSJQGJjLjI GOGQI GdGeOGOGJ GdOhdjI, GdGOGQI GdeGdjI GdOhdjI, GOGQI MGVfGJ GdGYeGd GdOhdjI, efgL GdGNdGbjGJ aj GdGOGQI GdOhdjI, eOGNd eeGQSI GdGNdGbjGJ aj GdGOGQI GdOhdjIs
(3HHdjhZQGajG(B: (3U(B.507s
Keywords: (3GOGQI GdGYeGds; (3GdGOGQIs; (3GdGSJQGJjLjIs; (3Gdbhi GdYGedIs; (3GdbjGOIs